Financial Globalization, Output Gap and Foreign Output Gap on inflation: Evidenced from Developing Economies - Muhammad Azhar Bhatti (Journal of Accounting and Finance in Emerging Economies, 2021)
This paper covers previous studies' deficiencies and re-examine the theoretical model using a heterogeneous panel GMM technique, which overcomes cross-section dependency. In the current sample of developing nations, developed two models'; model 1 consists of the domestic output gap, and the second model includes the foreign output gap. According to model 1, foreign globalization and imports boost the inflation level in developing countries and disaggregation analysis (low, lower-middle, and upper-middle-income countries). The output gap impedes inflation in overall, lower-middle, and upper-middle-income countries, while it boosts inflation in low-income nations. And unemployment level increases the inflation rate in the overall and middle-income groups, while in low- and high-income countries, it decreases. According to the second model, foreign globalization and the foreign output gap boost overall low-income, middle-income, and upper-middle-income groups. While import reduces the inflation level globally, while in low-income, middle-income, and upper-middle-income groups, it increases inflation. Finally, the unemployment level boosts the global inflation level and as well as in low income, and it impedes inflation rate in upper-middle-income group. Despite this, there is considerable variation in countries' effect, perhaps due to differences in political institutions' quality, central bank independence, exchange rate systems, financial development, and legal traditions.